2015
DOI: 10.1017/s0031182015000463
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence and geographic spread of the cardiopulmonary nematode Angiostrongylus vasorum in fox populations in Great Britain

Abstract: The nematode Angiostrongylus vasorum is becoming more widely recorded globally, and is of increasing concern as a cause of disease in dogs. Apparent geographic spread is difficult to confirm due to a lack of standardized disease recording systems, increasing awareness among veterinary clinicians, and recent improvements in diagnostic technologies. This study examines the hypothesis that A. vasorum has spread in recent years by repeating the methods of a previous survey of the fox population. The hearts and lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 41 publications
3
70
0
Order By: Relevance
“…This has changed remarkably over the last decade, and the disease is now very commonly diagnosed. Besides increased veterinary practitioner awareness, factors underlying this trend could be effect of longterm climate change on intermediate host availability and/or parasite development rate, increasing dog movement, or increasing transmission through the fox population (Taylor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This has changed remarkably over the last decade, and the disease is now very commonly diagnosed. Besides increased veterinary practitioner awareness, factors underlying this trend could be effect of longterm climate change on intermediate host availability and/or parasite development rate, increasing dog movement, or increasing transmission through the fox population (Taylor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In four of these eight dogs also arterial thrombi could be found. Growing prevalence in dogs and wildlife has been reported for A. vasorum (Taylor et al 2015, Barutzki et al 2017. There is also evidence for a growing infection rate in snails (Aziz et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A commercial antigen test for dog serum is now also available (AngioDetectTM, IDEXX Laboratories, Ludwigsburg, Germany). Epidemiological surveys indicate that the prevalence of A. vasorum infection in dogs and foxes is increasing in various European countries (Traversa et al 2013, Taylor et al 2015. A significant increase in the prevalence of A. vasorum from 0.9 % in 2004 -2006 to 1.8 % in 2012 -2016 was found in a retrospective analysis of canine faecal samples from Germany (Barutzki et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This may reveal higher prevalence rates, a regional spread, or a combination of both. One of the first studies to look into this was a comparison of the prevalence and regional distribution of A. vasorum studied in a fox population in the UK, where data from 2005(Morgan et al 2008 were compared with data from 2013/2014 using identical methods (Taylor et al 2015). It was concluded that the prevalence of A. vasorum increased from 7.3% to 18.3% (exact binomial confidence limits 14.9 -22.3).…”
Section: Introductionmentioning
confidence: 99%